MODERN METHODS OF ENTERPRISE FINANCIAL MANAGEMENT - Muydinov Muhammadsardor Abdukayum ugli (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article is devoted to the study of financial management methods in the enterprise. The concept of financial management in the enterprise is analyzed. The process of forming the financial result of the enterprise is presented. The main methods of financial management at the enterprise are studied.